Dukungan Sosial Suami, Konflik Peran Ganda dan Stress Kerja Wanita Karir - Ardiyansyah, Rahmat Yahya; Meiyuntariningsih, Tatik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
Husband social support, multiple of role conflict, and job stress examined in acorrelational quantitative research. Subjects were 50 Women’s Careerist. Researcherdeveloped two research instrument of measurement, namely the scale of job stress andthe scale of husband social support. Data of study variables were analyzed with themultiple regression. The results of the analysis are: 1) Values of R = 0,440 and F =5,627 and p = 0,006 (p < 0,01) showed that correlation of husband social support andmultiple of role conflict with job stress among Woman’s Careerist simultaneously is mostsignificant, 2) Partial regressions coefficient B of husband social support = – 0,143 andp = 0,381 (p > 0,05) shows no correlation of husband social support with job stressamong Women’s Careerist; 3) Partial regressions coefficient B of multiple of roleconflict = 0,206 and p = 0,006 (p < 0,01) shows correlation multiple of role conflictwith job stress is positive and most significant.Keywords : husband social support, multiple role conflict, job stress, Women’s Careerist.